Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element
By using a liquid crystal alignment agent composed of polyamic acid ester and polyamic acid of a specific structure, the problem of insufficient brush wear resistance in the process of high refinement of the liquid crystal representation element is solved, and the high brush wear resistance of the liquid crystal alignment film is achieved. Stability and charge relieving performance reduces flicker levels and improves storage stability.
Patent Information
- Application Number
- CN201680080101.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-11-25
- Filing Date
- 2016-11-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2036-11-24
AI Technical Summary
During the high-refining process of existing liquid crystal representation components, the brush wear resistance is insufficient, resulting in scratching and scratching problems. It is difficult to achieve the stability of liquid crystal orientation, the easing of charge accumulation and the optimization of flickering levels.
Using a liquid crystal alignment agent containing polyamic acid ester and polyamic acid with specific repeating units, the brush wear resistance, stability and charge relief properties of the liquid crystal alignment film are improved by optimizing its chemical structure and composition ratio, thereby reducing liquid crystal Indicates the flashing level of the component.
The high brush wear resistance, stability and rapid charge relief of the liquid crystal orientation film are achieved, which reduces the flickering level of the liquid crystal display element and improves its storage stability.
Smart Images

Figure CN108604027B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal aligning agent for producing a liquid crystal aligning film, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element having the liquid crystal aligning film. Background Art
[0002] At present, liquid crystal display elements are widely used in the image display part of a large number of devices such as digital cameras, personal computers, portable terminals, and televisions. Such a liquid crystal display element is formed into a structure in which a liquid crystal composition with fluidity is clamped and sealed by two supporting substrates, and a liquid crystal orientation film for orienting the liquid crystal molecules is provided on the surface of the aforementioned substrate in contact with the liquid crystal. The liquid crystal orientation film is generally produced by a process of coating a liquid crystal orientation agent on the aforementioned substrate. In addition, in the case of orienting the liquid crystal molecules in the in-plane direction of the substrate, the film obtained by the liquid crystal orientation agent is subjected to a brushing treatment, a photo-orientation treatment, and the like.
[0003] The basic property required by the liquid crystal alignment film is to orient the liquid crystal molecules in a specified direction, but in order to achieve high-performance liquid crystal display elements, it is also necessary to improve various other properties. Furthermore, in stable industrial production, the properties of the liquid crystal alignment agent, such as coating properties and storage stability, also become important. For example, Patent Document 1 discloses a liquid crystal alignment agent for the purpose of providing a liquid crystal alignment film that is not prone to scratches and scratches of the film caused by brushing. Moreover, Patent Document 2 discloses a liquid crystal alignment agent for the purpose of providing a liquid crystal alignment film that can suppress the misalignment of the brushing direction and the orientation direction of the liquid crystal on the basis of the brushing resistance of the film, has a high voltage retention rate when forming a liquid crystal display element, and can quickly relax the accumulated charge.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. WO2010 / 053128 Pamphlet
[0007] Patent Document 2: International Publication No. WO2015 / 122413 Pamphlet Summary of the invention
[0008] Problem that the invention aims to solve
[0009] With the increasing performance of liquid crystal display elements in recent years, liquid crystal alignment films are required to achieve various properties at a higher level than before. For example, as liquid crystal display elements are highly refined, scratches and scratches that are smaller than before are gradually becoming a problem in terms of brush resistance. In addition, it is also required to achieve a variety of other properties at the same time.
[0010] From the above, the object of the present invention is to provide: a liquid crystal orientation film that can obtain abrasion resistance, excellent stability of liquid crystal orientation, and rapid relaxation of charge accumulation in a liquid crystal display element, and further a liquid crystal orientation film with small flicker (flicker level) just after the liquid crystal display element is driven, and a liquid crystal orientation agent with excellent storage stability.
[0011] Solutions for solving problems
[0012] The present inventors have made repeated studies and, as a result, have completed the present invention, the gist of which is as follows.
[0013] A liquid crystal aligning agent characterized by containing the following (A) component and (B) component.
[0014] (A) Component: Polyamic acid ester containing a repeating unit represented by the following formula (1) and a repeating unit represented by the following formula (2).
[0015] (B) Component: a polyamic acid having a repeating unit represented by the following formula (3).
[0016]
[0017] (In formula (1) and formula (2), multiple R 1 Each independently represents an alkyl group having 1 to 6 carbon atoms, and the plurality of R 2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, Y 1 is a divalent organic group represented by the following formula (Y1-1), Y 2 It is a divalent organic group represented by the following formula (Y2-1).
[0018]
[0019] In formula (Y1-1), two R 3 Each independently represents a single bond, -O-, -S-, -OCO-, or -COO-, and the two R 4 are each independently an alkylene group having 1 to 3 carbon atoms, R 5 is an oxygen atom or a sulfur atom.
[0020]
[0021] In formula (Y2-1), A 1 and A 5 are each independently a single bond, a methylene group, an alkylene group having 2 to 5 carbon atoms, an azetidinyl group, a pyrrolidinediyl group, or a piperidinediyl group, 1 and B 2 are each independently a single bond, -O-, -COO-, -OCO-, -CONH-, -NHCO-, -CONCH3-, or -NCH3CO-, A2 and A 4 are each independently a single bond, a methylene group, or an alkylene group having 2 to 5 carbon atoms, 3 is a methylene group or an alkylene group having 2 to 6 carbon atoms, a is 0 or 1, R is a hydrogen atom or a methyl group, and D is a protecting group which is substituted with a hydrogen atom by heat.
[0022]
[0023] In formula (3), X is a tetravalent organic group, Y is a divalent organic group, and R 6 It is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0024] Effects of the Invention
[0025] According to the present invention, there can be provided: a liquid crystal orientation film which is resistant to brushing, has excellent stability in liquid crystal orientation, and has a fast relaxation of charge accumulation in a liquid crystal display element, and further a liquid crystal orientation film which has small flicker (flicker level) just after the liquid crystal display element is driven, and a liquid crystal orientation agent which has excellent storage stability; a liquid crystal orientation film obtained from the liquid crystal orientation agent; and a high-performance liquid crystal display element having the liquid crystal orientation film. DETAILED DESCRIPTION
[0026] <Polyamic acid ester (A)>
[0027] The polyamic acid ester which is said (A) component is polyamic acid ester containing the repeating unit represented by said formula (1) and the repeating unit represented by following formula (2).
[0028] In formula (1) and formula (2), multiple R 1 Each independently represents an alkyl group having 1 to 6 carbon atoms, preferably a methyl group or an ethyl group. 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, preferably a hydrogen atom or a methyl group.
[0029] In formula (1), Y 1 It is a divalent organic group represented by the following formula (Y1-1).
[0030]
[0031] In formula (Y1-1), R 3 , R 4 , R 5 As defined above, where R 3 Preferred are single bonds, -O-, R 4 Preferably, methylene, R 5 An oxygen atom is preferred.
[0032] The following are examples of Y1 Specific examples are shown, but the present invention is not limited to these.
[0033]
[0034]
[0035] Among the above, (Y1-1-1) to (Y1-1-8) are preferred from the viewpoint of the orientation stability of the liquid crystal. The repeating unit represented by formula (1) is preferably present in an amount of 1 to 70 mol%, more preferably 5 to 50 mol%, of all repeating units contained in the polyamic acid ester as the component (A).
[0036] In the above formula (2), Y 2 It is a divalent organic group represented by the following formula (Y2-1).
[0037]
[0038] In formula (Y2-1), A 1 , A 5 , B 1 , B 2 , A 2 , A 3 , A 4 , R, and a are as defined above. 1 , A 5 A is preferably a single bond, a methylene group, an ethylene group or a propylene group. 1 or A 5 In the case of an aliphatic heterocycle such as azetidinediyl, pyrrolidinediyl or piperidinediyl, azetidine-1,3-diyl, pyrrolidine-1,3-diyl or piperidine-1,4-diyl is preferred, and it is more preferred that the nitrogen atom in the ring is bonded to the adjacent benzene ring.
[0039] In addition, B 1 and B 2 A is preferably a single bond or -O-. 2 and A 4 A single bond, methylene, ethylene, or propylene is preferred. 3 Preferably, ethylene is used. Preferably, a is 0. Preferably, R is a hydrogen atom.
[0040] In formula (Y2-1), D is a protective group substituted with a hydrogen atom by heat. From the viewpoint of the storage stability of the liquid crystal aligning agent, it is suitable to be a group that does not leave at room temperature and leaves and is substituted with a hydrogen atom under heating in the production process of the liquid crystal alignment film. As a preferred leaving temperature, it is 80 to 200°C, more preferably 100 to 200°C, and particularly preferably 150 to 200°C. As specific examples of such groups, 1,1-dimethyl-2-chloroethoxycarbonyl, 1,1-dimethyl-2-cyanoethoxycarbonyl, tert-butoxycarbonyl, or 9-fluorenylmethoxycarbonyl, etc., preferably tert-butoxycarbonyl or 9-fluorenylmethoxycarbonyl, particularly preferably tert-butoxycarbonyl.
[0041] In the divalent organic group represented by the above formula (Y2-1), A 1 ~A 5 , B 1 , B 2 Preferred combinations of and a include combinations of Type 1 to Type 3 shown below, with Type 1 or Type 2 being more preferred, and Type 1 being particularly preferred.
[0042] Type 1: A 1 and A 5 is independently a single bond, a methylene group, or an alkylene group having 2 to 5 carbon atoms, 1 and B 2 are independently a single bond, -O-, -COO-, -OCO-, -CONH-, -NHCO-, -CONCH3-, or -NCH3CO-, A 2 and A 4 A is independently a methylene group or an alkylene group having 2 to 5 carbon atoms, 3 is a methylene group or an alkylene group having 2 to 6 carbon atoms, and a is 0 or 1.
[0043] More preferably, A 1 and A 5 All are single bonds, B 1 and B 2 are independently a single bond or -O-, A 2 and A 4 A is independently a methylene group or an alkylene group having 2 to 5 carbon atoms, 3 is a methylene group or an alkylene group having 2 to 6 carbon atoms, and a is 0 or 1.
[0044] Type 2: A 1 and A 5 are independently a single bond, azetidinediyl, pyrrolidinediyl, or piperidinediyl, B 1 and B 2 All are single bonds, A 2 and A 4are independently methylene or alkylene having 2 to 5 carbon atoms, and a is 0. More preferably, A 1 is azetidinediyl, pyrrolidinediyl, or piperidinediyl, A 2 is a methylene group or an alkylene group having 2 to 5 carbon atoms, 4 , A 5 , B 1 and B 2 is a single bond, and a is 0.
[0045] Type 3: A 1 , A 2 , A 4 , A 5 , B 1 , B 2 A is a single bond 3 It is a methylene group or an alkylene group having 2 to 6 carbon atoms, and a is 1.
[0046] The following are examples of Y 2 Specific examples of , but the present invention is not limited to these. It should be noted that D in the following structure has the same definition as that of formula (Y2-1).
[0047]
[0048]
[0049]
[0050] The (content) ratio of the repeating unit represented by Formula (2) is preferably 1 to 70 mol% in all the repeating units contained in the polyamic acid ester which is the (A) component, and more preferably 5 to 50 mol%.
[0051] In the polyamic acid ester as the component (A), the preferred ratio of the repeating unit represented by the formula (1) to the repeating unit represented by the formula (2) is 1:10 to 10:1, more preferably 1:6 to 6:1 in terms of molar ratio. In addition, among all the repeating units contained in the polyamic acid ester as the component (A), the sum of the repeating unit represented by the formula (1) and the repeating unit represented by the formula (2) is preferably 15 mol% or more, more preferably 30 mol% or more.
[0052] The polyamic acid ester as the component (A) may have repeating units other than the above formula (1) and formula (2). The structure of the repeating unit other than formula (1) and formula (2) is not particularly limited, but specific examples thereof are preferably repeating units represented by the following formula (4).
[0053]
[0054] In formula (4), R 1 , R2 Same definition as in formula (1), Y 3 represents a divalent organic group other than the above-mentioned formula (Y1-1) and formula (Y2-1). 3 The structure of is not particularly limited as long as it is a divalent organic group other than the above-mentioned formula (Y1-1) and formula (Y2-1). Specific examples of preferred structures are shown below, but the present invention is not limited to these.
[0055]
[0056] Among the above structures, (Y-5), (Y-10) to (Y-16), (Y-18), (Y-24) to (Y-29) and the like are particularly preferred.
[0057] The polyamic acid ester as the component (A) can be obtained by a known synthesis method. As an example, the following method can be cited: a method of polycondensing a tetracarboxylic acid derivative component containing a compound represented by the following formula (1a) with a diamine component containing a compound represented by the following formula (1b) and (2b); or a method of polyadding a tetracarboxylic dianhydride component containing a compound represented by the following formula (1a') with a diamine component containing a compound represented by the following formula (1b) and (2b) to obtain a polyamic acid, and then esterifying the carboxyl group.
[0058]
[0059] H2N-Y 1 -NH2 (1b) H2N-Y 2 -NH2 (2b)
[0060] In the formula, R is a hydroxyl group or a chlorine atom, R 1 , R 2 , Y 1 Same definition as in formula (1), Y 2 The same definition as in formula (2).
[0061] (A) In the liquid crystal aligning agent of this invention, although the molecular weight of the polyamic acid ester which is a component is not specifically limited, It is preferable that it is 2000-500000, More preferably, it is 5000-300000, More preferably, it is 10000-100000.
[0062] <Polyamic acid (B)>
[0063] The polyamic acid as the component (B) has a repeating unit represented by the following formula (3). The structure of the formula (3) contained in the polyamic acid may be one type or two or more types.
[0064]
[0065] In formula (3), X is a tetravalent organic group, Y is a divalent organic group, and R 6 It is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0066] The polyamic acid having the repeating unit represented by the above formula (3) can be obtained, for example, by polycondensing at least one compound represented by the following formula (3a) and at least one compound represented by the following formula (3b). Therefore, X in formula (3) may include structures corresponding to all the compounds represented by formula (3a). Similarly, Y and R in formula (3) 6 The structures corresponding to all the compounds represented by formula (3b) may also be included.
[0067]
[0068] X, Y, and R in formula (3a) and formula (3b) 6 Respectively with X, Y, R in formula (3) 6 The same definition.
[0069] Specific examples of preferred structures of X in formula (3) are shown below, but the present invention is not limited to these.
[0070]
[0071] In the above (X-1), R 7 ~R 10 Each is independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0072] X in the above formula (3) is preferably at least one selected from the group consisting of (X-1) to (X-14) above, and is particularly preferably selected from R in the above (X-1). 7 ~R 10 At least one of the group consisting of a structure consisting entirely of hydrogen atoms, (X-2), (X-3), (X-5), (X-6), (X-7), (X-8), (X-10), (X-11), and (X-14).
[0073] The structure of Y in formula (3) is not particularly limited as long as it is a divalent organic group. From the viewpoint of improving the flicker (flicker level) just after the liquid crystal display element is driven, Y preferably does not contain a repeating unit of formula (Y1-1) or formula (Y2-1).
[0074] More specifically, Y is preferably a divalent organic group selected from the group consisting of the following (i) to (iii).
[0075] (i) The structure represented by the following (c-1) or (c-2).
[0076] (ii) A combination of structures selected from the following (c-1) to (c-4).
[0077] (iii) A bonding group selected from the following (d-1) to (d-3) is contained in the middle of a combination of structures selected from the following (c-1) to (c-4).
[0078]
[0079] In formula (c-1), R represents a hydrogen atom, a methyl group, or a carboxyl group.
[0080] Among the above, the combination of structures selected from the group consisting of (c-1) to (c-4) may be a combination using multiple identical structures. In addition, the bonding groups selected from the group consisting of (d-1) to (d-3) are not adjacent to each other. The molecular weight of the divalent organic group selected from the group consisting of (i) to (iii) is more preferably 1000 or less. As specific examples of the above-mentioned Y, the aforementioned (Y-1) to (Y-34) etc. can be cited, but the present invention is not limited to these. Among them, particularly preferred are (Y-5), (Y-8), (Y-9), (Y-12), (Y-17), (Y-18) to (Y-20), or (Y-29).
[0081] In the liquid crystal aligning agent of the present invention, the molecular weight of the polyamic acid as the component (B) is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, further preferably 10,000 to 100,000 in terms of weight average molecular weight.
[0082] <Liquid crystal alignment agent>
[0083] The mass (content) ratio (polyamic acid ester / polyamic acid) of the polyamic acid ester (A) and the polyamic acid (B) contained in the liquid crystal aligning agent of this invention is preferably 1 / 9 to 9 / 1, more preferably 2 / 8 to 8 / 2.
[0084] The liquid crystal aligning agent of the present invention is preferably in the form of a solution containing polyamic acid ester (A) and polyamic acid (B). In the above case, the total content of polyamic acid ester (A) and polyamic acid (B) can be appropriately changed according to the setting of the thickness of the liquid crystal aligning film to be formed, and from the aspect of forming a uniform and defect-free coating film, it is preferably 0.5% by mass or more of the entire liquid crystal aligning agent, and from the aspect of the storage stability of the solution, it is preferably 15% by mass or less. In particular, 0.5 to 10% by mass, particularly preferably 1 to 10% by mass.
[0085] The organic solvent contained in the liquid crystal aligning agent of the present invention is not particularly limited as long as the polymer components of polyamic acid ester (A) and polyamic acid (B) are uniformly dissolved. If its specific example is given, N, N-dimethylformamide, N, N-diethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, 2-pyrrolidone, N-vinyl-2-pyrrolidone, dimethyl sulfoxide, dimethyl sulfone, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, 3-methoxy-N, N-dimethylpropionamide, etc. can be given. They can be used in one or in combination of two or more.
[0086] It should be noted that, from the viewpoint of compatibility of the polyamic acid ester (A) and the polyamic acid (B) contained in the liquid crystal aligning agent of the present invention, the content ratio of N-methyl-2-pyrrolidone is preferably 30 to 80% by mass relative to the total weight of the liquid crystal aligning agent. In addition, even a solvent that cannot uniformly dissolve the polymer component alone can be mixed in the above-mentioned organic solvent as long as it is within the range where the polymer does not precipitate.
[0087] The liquid crystal aligning agent of the present invention may also contain a solvent for improving the uniformity of the coating film when the liquid crystal aligning agent is applied to the substrate in addition to an organic solvent. The above-mentioned solvent generally uses a solvent with a low surface tension compared to the above-mentioned organic solvent. If its specific example is given, ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, ethyl carbitol acetate, ethylene glycol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, butyl cellosolve acetate, dipropylene glycol, 2-(2-ethoxy propoxy) propanol, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, etc. can be given. These solvents can be used in combination of 2 kinds.
[0088] The liquid crystal aligning agent of the present invention may contain various additives such as a silane coupling agent, a crosslinking agent, and an imidization accelerator.
[0089] The silane coupling agent may be added for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate. In addition, the silane coupling agent may be one kind or a combination of two or more kinds. The content of the silane coupling agent is preferably 0.01 to 5.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, relative to 100 parts by mass of the polymer component.
[0090] Specific examples of silane coupling agents are listed below, but are not limited to these. Amine-based silane coupling agents such as 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-phenylaminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and 3-aminopropyldiethoxymethylsilane; vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, and vinyltri(2-methoxyethoxy)silane; Vinyl silane coupling agents such as alkenylmethyldimethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, allyltrimethoxysilane, and p-phenylenetrimethoxysilane; epoxy silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; 3-methacryloxypropyl Methacrylic silane coupling agents such as methyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane; acrylic silane coupling agents such as 3-acryloxypropyltrimethoxysilane; urea-based silane coupling agents such as 3-ureidopropyltriethoxysilane; sulfide-based silane coupling agents such as bis(3-(triethoxysilyl)propyl)disulfide and bis(3-(triethoxysilyl)propyl)tetrasulfide 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-octanoylthio-1-propyltriethoxysilane and other mercapto-based silane coupling agents; 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane and other isocyanate-based silane coupling agents; triethoxysilylbutylaldehyde and other aldehyde-based silane coupling agents; triethoxysilylpropylmethylcarbamate, (3-triethoxysilylpropyl)-tert-butylcarbamate and other carbamate-based silane coupling agents.
[0091] The crosslinking agent can be used for the purpose of improving the film strength of the liquid crystal alignment film. In addition, the crosslinking agent can be one kind or a combination of two or more kinds. The amount of the crosslinking agent is preferably 0.1 to 50 parts by mass, more preferably 1 to 20 parts by mass relative to 100 parts by mass of the polymer component.
[0092] Examples of the crosslinking agent include: a crosslinking compound having an epoxy group, an isocyanate group, an oxetane group, a cyclocarbonate group, or a hydroxyalkylamide group; a crosslinking compound having at least one substituent selected from the group consisting of a hydroxyl group, a hydroxyalkyl group, and a lower alkoxyalkyl group; or a crosslinking compound having a polymerizable unsaturated bond, etc. It is preferred that the crosslinking compound has two or more of these substituents and polymerizable unsaturated bonds.
[0093] Specific examples of the crosslinking agent are given below, but are not limited to these. Examples of the crosslinking compound having an epoxy group or an isocyanate group include bisphenol acetone glycidyl ether, phenol novolac epoxy resin, cresol novolac epoxy resin, isocyanuric acid triglycidyl ester, tetraglycidyl aminodiphenylene, tetraglycidyl-m-phenylenediamine, tetraglycidyl-1,3-bis(aminoethyl)cyclohexane, tetraphenyl glycidyl ether ethane, triphenyl glycidyl ether ethane, bisphenol hexafluoroacetyl diglycidyl ether, 1,3-bis(1-(2,3-epoxypropoxy)-1-trifluoromethyl-2,2,2-trifluoromethyl)benzene, 4,4-bis(2,3-epoxypropoxy)octafluorobiphenyl, triglycidyl -p-aminophenol, tetraglycidyl meta-phenylenediamine, 2-(4-(2,3-epoxypropoxy)phenyl)-2-(4-(1,1-bis(4-(2,3-epoxypropoxy)phenyl)ethyl)phenyl)propane, 1,3-bis(4-(1-(4-(2,3-epoxypropoxy)phenyl)-1-(4-(1-(4-(2,3-epoxypropoxy)phenyl)-1-methylethyl)phenyl)ethyl)phenoxy)-2-propanol, etc.
[0094] Examples of crosslinkable compounds having an oxetane group include crosslinkable compounds represented by formulas [4a] to [4k] described in International Publication No. WO2011 / 132751, pages 58 to 59. Examples of crosslinkable compounds having a cyclocarbonate group include crosslinkable compounds represented by formulas [5-1] to [5-42] described in International Publication No. WO2012 / 014898, pages 76 to 82.
[0095] Examples of crosslinking compounds having a hydroxyalkylamide group include the crosslinking compounds described in [Chemical 35] on page 23 of International Publication WO2015 / 072554. Examples of crosslinking compounds having at least one substituent selected from the group consisting of a hydroxyl group and an alkoxy group include the crosslinking compounds represented by formulas [6-1] to [6-48] described in pages 62 to 66 of International Publication WO2011 / 132751.
[0096] Examples of the crosslinkable compound having a polymerizable unsaturated bond include the crosslinkable compounds described in
[0112] to
[0113] on pages 58 to 59 of International Publication No. WO2015 / 060357.
[0097] The imidization accelerator can be used for the purpose of making the imidization reaction of polyamic acid ester (A) and polyamic acid (B) efficiently carried out when the coating film of the liquid crystal aligning agent of the present invention is fired. The amount of the imidization accelerator is preferably 0.01 mole or more, more preferably 0.05 mole or more, and more preferably 0.1 mole or more relative to 1 mole of amic acid site and amic acid ester site where imidization reaction can occur. In addition, from the viewpoint of reducing the adverse effects caused to each characteristic of the liquid crystal alignment film to a minimum, the imidization accelerator itself remaining in the film after firing is preferably less than 2 moles, more preferably less than 1 mole, and more preferably less than 0.5 mole.
[0098] Specific examples of the imidization accelerator include compounds represented by formulae (B-1) to (B-17) described on page 29 of International Publication No. WO2010 / 114103, but are not limited thereto.
[0099] <Liquid crystal alignment film>
[0100] The liquid crystal alignment film of the present invention is a liquid crystal alignment film obtained by using the liquid crystal alignment agent of the present invention described above. The method for obtaining the liquid crystal alignment film can adopt a known method. For example, the following liquid crystal alignment film is a liquid crystal alignment film: the liquid crystal alignment agent is applied to a substrate and dried and fired to obtain a coating film, and the obtained coating film is subjected to a brushing treatment or irradiated with polarized ultraviolet rays, thereby giving a liquid crystal alignment ability to the liquid crystal alignment film.
[0101] As a substrate for coating a liquid crystal alignment agent, there is no particular limitation as long as it is a substrate with high transparency. Plastic substrates such as glass substrates, silicon nitride substrates, acrylic substrates, and polycarbonate substrates can be used. From the viewpoint of simplifying the process, it is preferred to use a substrate formed with an ITO electrode for liquid crystal driving. In addition, in a reflective liquid crystal display element, if it is only a single-sided substrate, an opaque object such as a silicon wafer can also be used, and the electrode in the above case can also use a material that reflects light such as aluminum. As a coating method for a liquid crystal alignment agent, spin coating, printing, inkjet, etc. can be cited.
[0102] The drying and firing steps after applying the liquid crystal alignment agent can select any temperature and time. Usually, in order to fully remove the organic solvent contained, it is dried at 50-120°C for 1 minute to 10 minutes, and then fired at 150-300°C for 5 to 120 minutes. The thickness of the coating film after firing is not particularly limited, but when it is too thin, the reliability of the liquid crystal display element is sometimes reduced, so it is 5 to 300 nm, preferably 10 to 200 nm.
[0103] As a method for performing an alignment treatment on the coating film, a brushing method, a photo-alignment treatment method, etc. are mentioned. When using it by a brushing method, the liquid crystal aligning agent of this invention is particularly useful.
[0104] <Liquid crystal display element>
[0105] The liquid crystal display element of the present invention is a liquid crystal display element having the above-mentioned liquid crystal alignment film. More specifically, after obtaining a substrate with a liquid crystal alignment film from the liquid crystal alignment agent of this embodiment by the above-mentioned method, a liquid crystal cell is prepared by a known method to form a liquid crystal display element.
[0106] If an example of the production of a liquid crystal unit is given, it is as follows. First, prepare a pair of substrates with a liquid crystal alignment film formed thereon. Then, make the liquid crystal alignment film surface the inner side, and after pasting the other substrate, inject the liquid crystal under reduced pressure and seal it. Alternatively, after dripping liquid crystal on the surface of the liquid crystal alignment film, the substrates can be pasted for sealing. At this time, in order to ensure space for filling the liquid crystal material between a pair of substrates, it is preferred to adopt the following means: provide columnar protrusions on one substrate, or scatter spacers on one substrate, or mix spacers in the sealing material, or combine them. The thickness of the spacer is preferably 1 to 30 μm, more preferably 2 to 10 μm.
[0107] As the above-mentioned liquid crystal material, nematic liquid crystal and smectic liquid crystal can be cited, among which nematic liquid crystal is preferred, and any of positive liquid crystal material and negative liquid crystal material can be used. Next, a polarizing plate is set. Specifically, it is preferred that a pair of polarizing plates are attached to the surface of the two substrates on the opposite side to the liquid crystal layer.
[0108] It should be noted that the liquid crystal alignment film and the liquid crystal display element of the present invention are not limited to the above description, and may be a liquid crystal alignment film and a liquid crystal display element prepared by other known methods. The process of obtaining a liquid crystal display element from a liquid crystal alignment agent is disclosed, for example, in Japanese Patent Publication No. 2015-135393, pages 17
[0074] to 19
[0081] , and is also disclosed in a large number of documents.
[0109] Example
[0110] The present invention is further described in detail by giving examples below. However, the present invention is not limited to these examples. The abbreviations of the compounds used hereinafter and the methods for measuring the properties are as follows.
[0111] <Abbreviation of compound>
[0112] In the following, "Boc" means tert-butoxycarbonyl.
[0113]
[0114] <Abbreviation of solvent>
[0115] NMP: N-methyl-2-pyrrolidone, BCS: butyl cellosolve
[0116] GBL: γ-butyrolactone, IPA: isopropyl alcohol
[0117] <Viscosity>
[0118] The viscosity of the polymer solution was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) at a sample volume of 1.1 mL, a conical rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0119] <Molecular weight>
[0120] The molecular weight of the polymer was measured using a GPC (normal temperature gel permeation chromatography) apparatus, and the number average molecular weight (hereinafter also referred to as Mn) and the weight average molecular weight (hereinafter also referred to as Mw) were calculated as polyethylene glycol or polyethylene oxide equivalents.
[0121] GPC equipment: Shodex (GPC-101)
[0122] Column: Shodex (KD803, KD805 in series), column temperature: 50°C
[0123] Eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) 30mmol / L, phosphoric acid·anhydrous crystals (orthophosphoric acid) 30mmol / L, tetrahydrofuran (THF) 10ml / L), flow rate: 1.0ml / min
[0124] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide manufactured by Tosoh Corporation (weight average molecular weight (Mw) of about 900,000, 150,000, 100,000, 30,000), and polyethylene glycol manufactured by Polymer Laboratories Ltd. (peak top molecular weight (Mp) of about 12,000, 4,000, 1,000). In order to avoid peak overlap, two samples were measured, namely, a sample in which four types of 900,000, 100,000, 12,000, and 1,000 were mixed, and a sample in which three types of 150,000, 30,000, and 4,000 were mixed.
[0125] <Brushing resistance evaluation>
[0126] After filtering the liquid crystal alignment agent with a 1.0 μm filter, spin-coated on a glass substrate with a transparent electrode, dried on a hot plate at 80 ° C for 5 minutes, and calcined at 230 ° C for 20 minutes to obtain a polyimide film with a thickness of 100 nm. The polyimide film was brushed with a rayon cloth once (roller diameter 120 mm, rotation speed 1000 rpm, moving speed 20 mm / second, and indentation 0.4 mm). The surface state of the film surface was observed with a confocal laser microscope, and the presence or absence of chips and scratches was observed at a magnification of 100 times. The situation where there was basically no chips or scratches was defined as "good" for evaluation, and the situation where a large amount of chips and brushing scratches were visible was defined as "bad" for evaluation.
[0127] <Production of Liquid Crystal Display Device>
[0128] First, prepare a substrate with electrodes. The substrate is a glass substrate with a size of 30mm×35mm and a thickness of 0.7mm. On the substrate, as the first layer, an IZO electrode constituting a counter electrode and having a solid pattern is formed. On the counter electrode of the first layer, as the second layer, a SiN (silicon nitride) film formed by a CVD method is formed. The film thickness of the SiN film of the second layer is 500nm, and it functions as an interlayer insulating film. On the SiN film of the second layer, as the third layer, a comb-shaped pixel electrode formed by patterning the IZO film is arranged to form two pixels, the first pixel and the second pixel. The size of each pixel is: 10mm in length and about 5mm in width. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the SiN film of the second layer.
[0129] The pixel electrode of the third layer has a comb-like shape composed of a plurality of "<"-shaped electrode elements with bent central portions. The width of each electrode element in the width direction is 3μm, and the interval between the electrode elements is 6μm. The pixel electrode forming each pixel is composed of a plurality of "<"-shaped electrode elements with bent central portions, so the shape of each pixel is not a rectangle, but a shape similar to a bold "<" that is bent in the central portion like the electrode elements. Furthermore, each pixel is divided into upper and lower parts with the central bent portion as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.
[0130] When comparing the first area and the second area of each pixel, the electrode elements constituting the pixel electrodes are formed in different directions. That is, when the brushing direction of the liquid crystal alignment film described later is used as a reference, in the first area of the pixel, the electrode elements of the pixel electrode are formed at an angle of +10° (clockwise), and in the second area of the pixel, the electrode elements of the pixel electrode are formed at an angle of -10° (clockwise). That is, the structure is as follows: in the first area and the second area of each pixel, the directions of the rotation action (plane switching) of the liquid crystal in the substrate surface induced by applying a voltage between the pixel electrode and the counter electrode are opposite to each other.
[0131] Next, the obtained liquid crystal alignment agent was filtered with a 1.0 μm filter and then spin-coated on the prepared substrate with electrodes and a glass substrate with an ITO film formed on the back as a counter substrate and a columnar spacer with a height of 4 μm. Next, after drying on a hot plate at 80°C for 5 minutes, it was calcined at 230°C for 20 minutes to form a coating with a thickness of 60 nm, and a polyimide film was obtained on each substrate. The polyimide film was brushed with a rayon cloth along the specified brushing direction (roller diameter 120 mm, rotation speed 500 rpm, moving speed 30 mm / second, and pressure 0.3 mm), and then ultrasonically irradiated in pure water for 1 minute and dried at 80°C for 10 minutes.
[0132] Afterwards, the two substrates with the above-mentioned liquid crystal alignment film were combined in such a way that their respective brushing directions became antiparallel, and the liquid crystal injection port was left, and the surrounding was sealed to make an empty cell with a cell spacing of 3.8 μm. After vacuum injection of liquid crystal (MLC-2041, MERCK CORPORATION) into the empty cell at room temperature, the injection port was sealed to form an antiparallel oriented liquid crystal cell. The obtained liquid crystal cell constituted an FFS mode liquid crystal display element. Afterwards, the obtained liquid crystal cell was heated at 120°C for 1 hour and left overnight for each evaluation.
[0133] <Evaluation of charge accumulation relaxation characteristics>
[0134] The evaluation of image sticking was performed using the following optical system, etc. The prepared liquid crystal unit was placed between two polarizing plates arranged so that the polarization axes were orthogonal, the LED backlight was turned on without applying voltage, and the arrangement angle of the liquid crystal unit was adjusted so that the brightness of the transmitted light was minimized.
[0135] Next, a VT curve (voltage-transmittance curve) was measured while applying an AC voltage with a frequency of 30 Hz to the liquid crystal cell, and the AC voltage at which the relative transmittance became 23% was calculated as the driving voltage.
[0136] In the image sticking evaluation, the liquid crystal cell was driven for 60 minutes while applying an AC voltage of 30 Hz at a relative transmittance of 23% and simultaneously applying a DC voltage of 1 V. Thereafter, the DC voltage was set to 0 V, and only the DC voltage was stopped, and the liquid crystal cell was driven for another 30 minutes in this state.
[0137] In the evaluation, if the relative transmittance dropped to 30% or less within 60 minutes from the start of DC voltage application, it was defined as "good". If it took more than 60 minutes for the relative transmittance to drop to 30% or less, it was defined as "poor".
[0138] Then, the image sticking evaluation according to the above method was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.
[0139] <Evaluation of Liquid Crystal Orientation Stability>
[0140] Using this liquid crystal cell, an AC voltage of 10 VPP was applied at a frequency of 30 Hz for 168 hours in a constant temperature environment of 60° C. Thereafter, the liquid crystal cell was left at room temperature for one day with the pixel electrode and the counter electrode short-circuited.
[0141] After placement, the liquid crystal unit is set between two polarizers configured in a manner that the polarization axes are orthogonal, the backlight is turned on without applying voltage, and the configuration angle of the liquid crystal unit is adjusted in a manner that the brightness of the transmitted light is minimized. Then, the rotation angle when the liquid crystal unit is rotated from the angle where the second area of the first pixel becomes the darkest to the angle where the first area becomes the darkest is calculated as angle Δ. Similarly, for the second pixel, the second area is compared with the first area to calculate the same angle Δ. Then, the average value of the angle Δ values of the first pixel and the second pixel is calculated as the angle Δ of the liquid crystal unit. When the value of the angle Δ of the liquid crystal unit exceeds 0.2 degrees, it is defined as "poor" for evaluation. When the value of the angle Δ of the liquid crystal unit does not exceed 0.2 degrees, it is defined as "good" for evaluation.
[0142] <Evaluation of flicker level immediately after driving>
[0143] The evaluation of image sticking was performed using the following optical system and the like.
[0144] The prepared liquid crystal unit is placed between two polarizing plates arranged so that their polarization axes are orthogonal, the LED backlight is turned on without applying voltage, and the arrangement angle of the liquid crystal unit is adjusted so that the brightness of the transmitted light is minimized.
[0145] Next, a VT curve (voltage-transmittance curve) was measured while applying an AC voltage with a frequency of 30 Hz to the liquid crystal cell, and the AC voltage at which the relative transmittance became 23% was calculated as the driving voltage.
[0146] In the determination of the flicker level, the LED backlight that was previously lit was temporarily turned off, and after being placed away from light for 72 hours, the LED backlight was turned on again. At the same time as the backlight was turned on, an AC voltage with a frequency of 30 Hz was applied with a relative transmittance of 23%, and the liquid crystal unit was driven for 60 minutes to track the flicker amplitude. For the flicker amplitude, the data acquisition / data recorder switch device 34970A (manufactured by Agilent Technologies) connected via a photodiode and an IV conversion amplifier reads the transmitted light of the LED backlight through the two polarizing plates and the liquid crystal unit between them. The flicker level was calculated using the following mathematical formula.
[0147] Flicker level (%) = {flicker amplitude / (2×z)}×100
[0148] In the above formula, z is the value obtained by reading the brightness when driven with an AC voltage of a frequency of 30 Hz at which the relative transmittance becomes 23% using the data acquisition / data logger switch device 34970A.
[0149] In the evaluation of the flicker level, if the flicker level is maintained below 3% for 60 minutes after the LED backlight is turned on and the AC voltage is applied, it is defined as "good". If the flicker level reaches 3% or more within 60 minutes, it is defined as "poor".
[0150] Then, the evaluation of the flicker level according to the above method was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.
[0151] <Evaluation of storage stability>
[0152] In the evaluation of storage stability, a change in viscosity of the prepared solution before and after storage at room temperature for one week was evaluated as "good" if it was less than 5 mPa·s, and as "poor" if it was 5 mPa·s or more.
[0153] <Synthesis example>
[0154] (Synthesis example 1)
[0155] In a 7 L separable flask equipped with a stirrer, 119 g (0.46 mol) of CE-1 was added, and then 2372 g of NMP was added and stirred to dissolve. Then, 146 g (1.44 mol) of triethylamine, 61 g (0.26 mol) of DA-1, 21 g (0.072 mol) of DA-3, and 49 g (0.14 mol) of DA-5 were added and stirred to dissolve.
[0156] While stirring this solution under water cooling, 362g (0.94mol) of DBOP was added, and 326g of NMP was further added, and it stirred at room temperature for 12 hours to obtain a solution of polyamic acid ester. The viscosity of this polyamic acid ester solution was 27.3mPa·s.
[0157] This polyamic acid ester solution was put into 20739g of IPA, and the obtained precipitate was filtered out. After washing this precipitate with methanol, it was dried under reduced pressure at a temperature of 100°C to obtain a powder of polyamic acid ester. The molecular weight of this polyamic acid ester was Mn=12200, Mw=21700.
[0158] NMP was added to the powder of the polyamic acid ester obtained so that a solid content concentration might become 12 weight%, and it was stirred at 50°C for 30 hours and dissolved to obtain a polyamic acid ester solution (PAE-1).
[0159] (Synthesis example 2)
[0160] In a 300 mL four-necked flask equipped with a stirrer, 6.85 g (26.3 mmol) of CE-1 was added, and then 140 g of NMP was added and stirred to dissolve. Then, 8.5 g (84.0 mmol) of triethylamine, 4.10 g (16.8 mmol) of DA-2, and 3.82 g (11.2 mmol) of DA-5 were added and stirred to dissolve.
[0161] While stirring this solution under water cooling, 20.7g (54.0mmol) of DBOP was added, and 19.2g of NMP was further added, and it stirred at room temperature for 12 hours to obtain a solution of polyamic acid ester. The viscosity of this polyamic acid ester solution was 31.4mPa·s.
[0162] This polyamic acid ester solution was put into 1218g of IPA, and the obtained precipitate was filtered out. After washing this precipitate with methanol, it was dried under reduced pressure at a temperature of 100°C to obtain a powder of polyamic acid ester. The molecular weight of this polyamic acid ester was Mn=11600, Mw=20500.
[0163] NMP was added to the powder of the polyamic acid ester obtained so that a solid content concentration might become 12 weight%, and it was stirred at 50 degreeC for 30 hours and it melt|dissolved, and the polyamic acid ester solution (PAE-2) was obtained.
[0164] (Synthesis example 3)
[0165] In a 5 L separable flask equipped with a stirring device and a nitrogen inlet tube, 243.9 g (1.22 mol) of DA-4 and 74.8 g (0.31 mol) of DA-2 were taken, 3154 g of a solvent (NMP:GBL = 50 wt%:50 wt%) was added, and the mixture was stirred while introducing nitrogen to dissolve.
[0166] While stirring the diamine solution under water cooling, 129.0 g (0.66 mol) of CA-2 and 166.8 g (0.77 mol) of CA-1 were added, and a solvent (NMP:GBL = 50 wt%: 50 wt%) was added so that the solid content concentration became 12 wt%, and the mixture was stirred at 50°C for 12 hours to obtain a polyamic acid solution (PAA-1). The viscosity of the polyamic acid solution was 310 mPa·s. In addition, the polyamic acid had Mn = 11700 and Mw = 24300.
[0167] (Synthesis Example 4)
[0168] In a 200 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, 4.1 g (20.4 mmol) of DA-4, 5.4 g (13.6 mmol) of DA-6 and 8.3 g (34.0 mol) of DA-2 were added with 173 g of NMP and stirred to dissolve them while introducing nitrogen.
[0169] While stirring the diamine solution under water cooling, 5.3 g (27.2 mmol) of CA-2 and 7.4 g (34.0 mmol) of CA-1 were added, and NMP was further added so that the solid content concentration became 15% by weight, and stirred at 50° C. for 12 hours to obtain a polyamic acid solution (PAA-2). The viscosity of the polyamic acid solution at a temperature of 25° C. was 530 mPa·s. In addition, the molecular weight of the polyamic acid was Mn=11700 and Mw=27200.
[0170] (Example 1)
[0171] In a 20 ml sample tube with a stirrer, 2.31 g of PAE-1 and 8.31 g of PAA-1 were taken, and 1.31 g of NMP, 2.38 g of GBL, 4.0 g of BCS, 1.2 g of an NMP solution containing 1 wt % of AD-1, and 0.60 g of AD-2 were added, and stirred with a magnetic stirrer for 30 minutes to obtain a liquid crystal aligning agent (A-1).
[0172] (Example 2)
[0173] In a 20 ml sample tube with a stirrer, 3.46 g of PAE-1 and 7.18 g of PAA-1 were taken, and 0.73 g of NMP, 2.38 g of GBL, 4.0 g of BCS, 1.2 g of an NMP solution containing 1 wt % of AD-1, and 0.60 g of AD-2 were added, and stirred with a magnetic stirrer for 30 minutes to obtain a liquid crystal aligning agent (A-2).
[0174] (Example 3)
[0175] In a 20 ml sample tube with a stirrer, 4.62 g of PAE-1 and 6.15 g of PAA-1 were taken, and 0.15 g of NMP, 2.38 g of GBL, 4.0 g of BCS, 1.2 g of an NMP solution containing 1 wt % of AD-1, and 0.60 g of AD-2 were added, and stirred with a magnetic stirrer for 30 minutes to obtain a liquid crystal aligning agent (A-3).
[0176] (Comparative Example 1)
[0177] In a 20 ml sample tube with a stirrer, 2.40 g of PAE-2 and 6.88 g of PAA-2 were taken, and 4.92 g of GBL, 4.0 g of BCS, 1.2 g of an NMP solution containing 1 wt % of AD-1, and 0.60 g of AD-2 were added, and stirred with a magnetic stirrer for 30 minutes to obtain a liquid crystal aligning agent (B-1).
[0178] The results are shown in Table 1. The liquid crystal aligning agent obtained above was used to evaluate the brushing resistance, the relaxation characteristics of charge accumulation, the stability of the liquid crystal alignment, the flicker level immediately after driving, and the storage stability.
[0179] [Table 1]
[0180]
[0181] As described above, the liquid crystal alignment film of the present invention showed good results in the evaluation of the brushing resistance, the evaluation of the afterimage erasure time, the evaluation of the stability of the liquid crystal alignment, and the evaluation of the flicker level immediately after driving.
[0182] Industrial Applicability
[0183] The liquid crystal aligning film obtained from the liquid crystal aligning agent of the present invention can be used in a wide range of liquid crystal display elements including IPS drive system and FFS drive system, which are required to realize various characteristics at higher levels than ever before.
[0184] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2015-229489 filed on November 25, 2015 are incorporated herein in their entirety and are incorporated as the disclosure of the specification of the present invention.
Claims
1. A liquid crystal alignment agent, characterized in that: Containing the following components (A) and (B), (A) component: a polyamic acid ester containing a repeating unit represented by the following formula (1) and a repeating unit represented by the following formula (2), wherein the content ratio, i.e., the molar ratio, of the repeating unit represented by the formula (1) to the repeating unit represented by the formula (2) in the polyamic acid ester of the (A) component is 1:10 to 10:1, (B) component: a polyamic acid having a repeating unit represented by the following formula (3), The mass content ratio of the component (A) to the component (B) is 1 / 9 to 9 / 1, In formula (1) and formula (2), multiple R 1 Each independently represents an alkyl group having 1 to 6 carbon atoms, and the plurality of R 2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, Y 1 is a divalent organic group represented by the following formula (Y1-1), Y 2 is a divalent organic group represented by the following formula (Y2-1), In formula (Y1-1), two R 3 Each independently represents a single bond, -O-, -S-, -OCO-, or -COO-, and the two R 4 are each independently an alkylene group having 1 to 3 carbon atoms, R 5 is an oxygen atom or a sulfur atom, In formula (Y2-1), A 1 and A 5 are each independently a single bond, a methylene group, an alkylene group having 2 to 5 carbon atoms, an azetidinyl group, a pyrrolidinediyl group, or a piperidinediyl group, 1 and B 2 are each independently a single bond, -O-, -COO-, -OCO-, -CONH-, -NHCO-, -CONCH3-, or -NCH3CO-, A 2 and A 4 are each independently a single bond, a methylene group, or an alkylene group having 2 to 5 carbon atoms, 3 is a methylene group or an alkylene group having 2 to 6 carbon atoms, a is 0 or 1, R is a hydrogen atom or a methyl group, and D is a 1,1-dimethyl-2-chloroethoxycarbonyl group, a 1,1-dimethyl-2-cyanoethoxycarbonyl group, a tert-butoxycarbonyl group or a 9-fluorenylmethoxycarbonyl group. In formula (3), X is a tetravalent organic group, Y is a divalent organic group, and R 6 It is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
2. The liquid crystal alignment agent according to claim 1, wherein Formula (Y1-1) is selected from the group consisting of (Y1-1-1) to (Y1-1-8) below, 3. The liquid crystal aligning agent according to claim 1 or 2, wherein: In formula (Y2-1), A 1 , A 2 , A 4 , A 5 , B 1 , B 2 A is a single bond 3 It is a methylene group or an alkylene group having 2 to 6 carbon atoms, and a is 1.
4. The liquid crystal aligning agent according to claim 1 or 2, wherein In formula (3), Y is a divalent organic group selected from the group consisting of the following (i), (iii) and (iii), (i) The structure represented by (c-1) or (c-2) below; (ii) a combination of structures selected from the group consisting of the following (c-1) to (c-4); (iii) a bonding group selected from the group consisting of the following (d-1) to (d-3) is contained in the middle of a combination of structures selected from the group consisting of the following (c-1) to (c-4); In formula (c-1), R represents a hydrogen atom, a methyl group, or a carboxyl group.
5. The liquid crystal alignment agent according to claim 4, wherein: In formula (3), X is at least one tetravalent organic group selected from the group consisting of (X-1) to (X-14) below, and in (X-1), R7 to R 10 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, 6. The liquid crystal aligning agent according to claim 1 or 2, wherein: The ratio of the repeating unit represented by Formula (1) or the ratio of the repeating unit represented by Formula (2) is 1 to 70 mol% of all the repeating units contained in the polyamic acid ester which is the (A) component.
7. The liquid crystal aligning agent according to claim 1 or 2, wherein: The total content of the (A) component and the (B) component is 0.5 to 15 mass % with respect to the entire liquid crystal aligning agent.
8. The liquid crystal aligning agent according to claim 1 or 2, wherein The component (B) is contained in an amount of 100 to 400 parts by mass based on 100 parts by mass of the component (A).
9. The liquid crystal alignment agent according to claim 1 or 2, wherein: Contains: an organic solvent selected from the group consisting of N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, 2-pyrrolidone, N-vinyl-2-pyrrolidone, dimethyl sulfoxide, dimethyl sulfone, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, and 3-methoxy-N,N-dimethylpropionamide.
10. The liquid crystal aligning agent according to claim 1 or 2, wherein It also contains: a silane coupling agent, a cross-linking agent, or an imidization accelerator. 11 . A liquid crystal aligning film obtained using the liquid crystal aligning agent according to claim 1 . 12 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 11 .
Citation Information
Patent Citations
Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display element, retardation film, and manufacturing method of retardation film
JP2015135393A
Vehicle brake device
JP2015229489A
Liquid crystal aligning agent
WO2010053128A1
Polyimide precursor composition containing polyamic alkyl ester
WO2010114103A1
Liquid-crystal alignment agent, liquid-crystal alignment film, and liquid-crystal display element
WO2011132751A1